Integration and search engine bias. - Cornière, Alexandre; Taylor, Greg (RAND Journal of Economics (Wiley-Blackwell), 2014)
We study the effects of integration between a search engine and a publisher. In a model in which the search engine (i) allocates users across publishers and (ii) competes with publishers to attract advertisers, we find that the search engine is biased against publishers that display many ads - even without integration. Integration can (but need not) lead to own-content bias. It can also benefit consumers by reducing the nuisance costs due to excessive advertising. Advertisers are more likely to suffer from integration than consumers. On net, the welfare effects of integration are ambiguous.